Application of Health Belief Model on Breast Self-Examination: A Meta-Analysis - Maranata Maranata; Eti Poncorini Pamungkasari; Rita Benya Adriani (Journal of Health Promotion and Behavior, 2020)
Background: Breast cancer is a type of cancer and the leading cause of cancer death in women. BSE is an early detection method for breast cancer. Health Belief Model is a model of health behavior that can predict women's interest in practicing BSE. This study aims to estimate the Health Belief Model's effect in the practice of BSE by meta-analysis.Subjects and Method: Meta-analysis was performed by searching for articles from the PubMed database, Springer Link, Elsevier, and Google Scholar. The keywords used were "health belief model," OR "health belief" OR "belief" AND "breast self-examination," OR "breast cancer screening." This study's inclusion criteria were full-text articles published in 2011-2020, a cross-sectional study design. Article analysis using RevMan 5.3 software.Results: There were 12 articles in total. The results showed that perceived benefits were strong (aOR= 1.02; 95% CI= 0.94-1.11; p= 0.590; I2= 73%), perceived barriers were weak (aOR = 1; 95% CI= 0.95-1.05; p= 0.920; I2= 87%).Conclusion: Perceived benefits and perceived barriers are not statistically significant in predicting BSE practice in women.Keywords: health belief model, perceived benefits, perceived barriers, BSECorrespondence: Maranata. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: maranataima@gmail.com. Mobile: 085867548771Journal of Health Promotion and Behavior (2020), 05(03): 221-231https://doi.org/10.26911/thejhpb.2020.05.03.08.